Curry-Odorants and Their Metabolites Transfer into Human Milk and Urine - Debong, Marcel; Homm, Ines; Gigl, Michael; Lang, Roman; Hofmann, Thomas; Büttner, Andrea; Dawid, Corinna; Loos, Helene (Molecular Nutrition & Food Research, 2024)
Scope: The excretion of dietary odorants into urine and milk is evaluated and the impact of possible influencing factors determined. Furthermore, the metabolic relevance of conjugates for the excretion into milk is investigated. Methods and Results: Lactating mothers (n = 20) are given a standardized curry dish and donated one milk and urine sample each before and 1, 2, 3, 4.5, 6, and 8 h after the intervention. The concentrations of nine target odorants in these samples are determined. A significant transition is observed for linalool into milk, as well as for linalool, cuminaldehyde, cinnamaldehyde, and eugenol into urine. Maximum concentrations are reached within 1 h after the intervention in the case of milk and within 2–3 h in the case of urine. In addition, the impact of glucuronidase treatment on odorant concentrations is evaluated in a sample subset of twelve mothers. Linalool, eugenol, and vanillin concentrations increased 3–77-fold in milk samples after treatment with β-glucuronidase. Conclusion: The transfer profiles of odorants into milk and urine differ qualitatively, quantitatively, and in temporal aspects. More substances are transferred into urine and the transfer needs a longer period compared with milk. Phase II metabolites are transferred into urine and milk.
CRIS-Team Scopus Importer:2024-04-19
Keywords: aroma; early flavor learning; glucuronides; odorant metabolism; stir bar sorptive extraction